Traumatic thoracolumbar fracture–dislocation in an infant: surgical management using posterior thoracolumbar instrumentation. Issue 8 (26th August 2020) - Alkhaibary, Ali; Khairy, Sami; Alshaya, Wael
Abstract: Spinal fracture–dislocation in the infantile population is a rare phenomenon, and its surgical management remains poorly discussed in the literature. This article reports a case of traumatic fracture–dislocation in an infant by outlining the surgical management and extensively reviewing the literature. An 8-month-old girl was involved in a motor vehicle accident and was ejected from the car through the windshield. Radiological imaging demonstrated a complete spinal cord injury at the level of T10 and a three-column fracture of T12-L1, with an evidence of kyphosis measuring 47° at the fracture site. Posterior thoracolumbar instrumentation, using the posterior cervical fixation set, was successfully performed. In experienced neurosurgical centers, posterior thoracolumbar instrumentation can be safely performed in infants with traumatic thoracolumbar fracture–dislocation. This allows for the correction of the kyphotic deformity, facilitation of the rehabilitation course and improvement in the health-related quality of life.